1989
DOI: 10.1017/s0305000900010394
|View full text |Cite
|
Sign up to set email alerts
|

The validity of a parent report instrument of child language at twenty months

Abstract: When carefully assessed and analysed, parent report can provide a valuable overall evaluation of children's language at 20 months. Norming information and validity coefficients are presented here for a vocabulary checklist assessment included in the Early Language Inventory. Normative data are provided for fullterm, preterm, and precocious samples, including selected vocabulatory subsets that are indicative of early language learning style. The vocabulary checklist has substantial validity as indexed by correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
241
1
13

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(272 citation statements)
references
References 6 publications
17
241
1
13
Order By: Relevance
“…These three different modes of assessing early grammar were all highly correlated in the Fenson et al study. More importantly still, the three measures correlate very highly with traditional laboratory measures of grammatical complexity (Dale, 1991;Dale et al, 1989), including correlations with MLU up to the statistical ceiling (i.e., as high as MLU correlates with itself in reliability studies). It is thus fair to conclude that these measures constitute a valid and reliable estimate of individual differences in grammatical development across the period from 16-30 months of age.…”
Section: Grammar and The Lexicon In Normally Developing Childrenmentioning
confidence: 89%
See 1 more Smart Citation
“…These three different modes of assessing early grammar were all highly correlated in the Fenson et al study. More importantly still, the three measures correlate very highly with traditional laboratory measures of grammatical complexity (Dale, 1991;Dale et al, 1989), including correlations with MLU up to the statistical ceiling (i.e., as high as MLU correlates with itself in reliability studies). It is thus fair to conclude that these measures constitute a valid and reliable estimate of individual differences in grammatical development across the period from 16-30 months of age.…”
Section: Grammar and The Lexicon In Normally Developing Childrenmentioning
confidence: 89%
“…After all that work we were surprised to find that, at least in this period of development, MLU is so highly correlated with other, more sophisticated measures, that there was no point in using any other estimate of grammar in correlational analyses with other variables; for a discussion of this point, see . 1994; Dale, 1991;Dale, Bates, Reznick, & Morisset, 1989;Fenson et al, 1993Fenson et al, , 1994Marchman & Bates, 1994 for review). Because many of the examples we will provide below rely on this instrument, some methodological details are in order.…”
Section: Grammar and The Lexicon In Normally Developing Childrenmentioning
confidence: 99%
“…These levels of agreement even surpass the levels reported by Camaioni et al (1991) forhearingparents of hearinginfants. Theseresults indicate that hearing parents of children with hearing loss can provide reliable information on the communicative behaviors of their children at home when they are guided by a structured questionnaire that presents a closed set of optional responses (Dale, Bates, Reznick, & Morisset, 1989). …”
mentioning
confidence: 82%
“…40 Moreover, despite differences in physician's and parents' views of developmental skills, agreement between the two is still high with a congruence ranging from 75 to 90%. [43][44][45] Parent-completed measures have additional advantages. A study showed that almost 70% of mothers were more worried about their child' s behavior or development than medical issues, but only slightly more than a quarter (28%)…”
Section: Introductionmentioning
confidence: 99%